Analisa Pengoptimalan Keuntungan pada Pabrik Tempe Menggunakan Metode Grafik - Celsania Rustiandini; Siska Rahmawati Sukma; Tya Nurhaliza; Dedek Kustiawati; Nazliyah Qur’ani (Publikasi Indonesia, 2022)
Mathematics is a science that plays an important role in various fields, including science and technology. Therefore, as the times progress, the economic problems that exist in everyday life become increasingly complex. By studying mathematics, these problems can be solved using linear programming. Linear programming is a way of solving optimization problems (maximizing or minimizing) by modeling them in the form of objective functions and constraint functions. Existing economic problems can be solved by several methods including graphical methods, elimination and substitution methods, mixed methods and simplex methods. In doing business, the thing that must be considered is the production process. This aims to maximize profits to be optimal. In this study the production process is an important thing that can affect a profit. The purpose of this research is to optimize the amount of tempeh production in order to obtain maximum profit. Graphical method is the method used in solving this problem. This research uses a literature study, which is carried out by collecting data from various sources such as books, journals, articles and other scientific works. The technique used to collect data in this study is by collecting data sources from various media, reading them and then starting to manage the data obtained from these sources.